Development of rubber compounds for machine-building purposes (Международный научный журнал «Инженер», 2026)
The influence of secondary raw materials of zinc production on the properties of rubbers based on SKI-3 andSKMS-30 ARKM-15 rubbers has been studied. The research results showed that when MCOM is introducedinto SKI-3-based rubber compounds in the ratio zinc oxide +BCOM 2.5+2.5 and 1.0+4.0, there are practicallyno changes in the kinetics of vulcanization. When using MCOM individually as part of elastomericcompositions, the optimal vulcanization time is reduced by 1.19 times compared to a rubber compoundcontaining zinc oxide. It can be every metal oxide in the MCOM composition that affects the vulcanization gridby its activity. For mixtures based on SKMS-30 ARKM-15, a similar dependence of the change in the kineticparameters of vulcanization is observed as for mixtures based on polyisoprene when a combination of activatorsis introduced in the same proportions. However, with a further increase in the MCOM content in the rubbercompound, the optimal vulcanization time is slightly reduced (by 1.07– 1.09 times) and an increase in thevulcanization rate is observed. Based on the results obtained, it was found that the introduction of VSOM intorubber compounds based on SKI-3 and SK(M)S-30 ARKM-15 in combination with zinc oxide in a ratio makesit possible to obtain rubber compounds and vulcanizates that are not inferior in properties to elastomericcompositions containing a traditional zinc oxide activator.